2008
DOI: 10.1111/j.1365-2486.2008.01654.x
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary carbon accumulation in a boreal oligotrophic minerogenic mire – a significant sink after accounting for all C‐fluxes

Abstract: Based on theories of mire development and responses to a changing climate, the current role of mires as a net carbon sink has been questioned. A rigorous evaluation of the current net C-exchange in mires requires measurements of all relevant fluxes. Estimates of annual total carbon budgets in mires are still very limited. Here, we present a full carbon budget over 2 years for a boreal minerogenic oligotrophic mire in northern Sweden (64111 0 N, 19133 0 E). Data on the following fluxes were collected: land-atmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
356
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 328 publications
(377 citation statements)
references
References 64 publications
19
356
1
1
Order By: Relevance
“…) (Nillson et al 2008;Wu et al 2013). On the other hand, similar values of cumulated R ECO were measured at Mer Bleue raised bog (Roulet et al 2007) and at Stordalen mixed mire (Bäckstrand et al 2010), specifically 230.0 and 150.0 g C-CO 2 m −2 yr −1…”
Section: Estimated Yearly Carbon Losssupporting
confidence: 58%
“…) (Nillson et al 2008;Wu et al 2013). On the other hand, similar values of cumulated R ECO were measured at Mer Bleue raised bog (Roulet et al 2007) and at Stordalen mixed mire (Bäckstrand et al 2010), specifically 230.0 and 150.0 g C-CO 2 m −2 yr −1…”
Section: Estimated Yearly Carbon Losssupporting
confidence: 58%
“…Glaser et al 1981;Pastor et al, 2003), although this was not particularly evident in the data collated here possibly due to the inclusion of a number of poor fen (e.g. Strack et al, 2008;Nilsson et al, 2008) and mixed mire systems in the dataset (Supplementary Table 2). …”
Section: Doc Fluxes From Natural Peatlandsmentioning
confidence: 82%
“…For example, Billett et al (2004) measured a waterborne carbon flux of 30 g C m -2 yr -1 , which they estimated was sufficient to turn their study site, a raised bog in Southern Scotland, from an apparent carbon sink (based on direct land-atmosphere fluxes alone) into an actual carbon source. A number of subsequent flux measurement studies in other near-natural peatlands Nilsson et al, 2008;Koehler et al, 2011), as well as further measurements at the same site (Dinsmore et al, 2012), confirm that waterborne carbon is, to varying degrees, a quantitatively important component of the carbon balance. The omission of waterborne fluxes leads to a systematic bias in calculated carbon balancesunder-estimating carbon losses from many ecosystems (e.g.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…However, our results correspond with those of Dinsmore et al (2010), which showed a peatland catchment losing 24% of NEE as DOC. Furthermore, in a Swedish mire complex the aquatic loss was 34% of the annual carbon uptake (Nilsson et al 2008). The proportion of peatland in Valkea-Kotinen is over 20% and the lake shores are histosols, which can increase lateral transport compared with mineral soils.…”
Section: Discussionmentioning
confidence: 99%